IMPACT OF ELECTRICAL VEHICLES CHARGING ON THE MAXIMUM DEMAND OF THE POWER GRID AND THE POLICES FOLLOWED TO CONFRONT IT - Dweikat, Talal Amjad Talal (An-Najah National University, 2025)
Abstract With the increasing number of electric vehicles and increased government adoption, challenges are mounting for electrical grids around the world. One of the most significant challenges is the rising demand for electrical grids and its impact on the maximum load, especially during peak hours. This research investigates the impact of the widespread deployment of electric vehicles on the grid's daily load curve, and the strategies that can be used to mitigate the stress on the grid. The user behavior of electric vehicles and their charging methods were studied through a questionnaire. The results obtained from the analysis of user data enable the identification of several important elements in this study. Data such as the prevalence of electric vehicles, the capacity of the chargers used, the average battery capacity available in the market, and the behavior of the electric charger user during usage times are all elements that help in studying the impact of the increase in electric vehicles and providing appropriate recommendations for each network separately. Using the results obtained from the user behavior study and drawing a daily load curve for new loads, it is possible to identify areas of high loads and how they are distributed across the network spatially and temporally. Determining the daily load curve for vehicle charging is the key point in providing recommendations for the use of network management strategies. To address these challenges, this study examines demand-side management (DSM) strategies such as demand response, load shifting, smart grid, and smart charging. Implementing DSM strategies enables the grid to handle increased electrical loads while maintaining network stability and quality. The study includes specific recommendations for increasing grid reliability and addressing the challenges of increased loads, including the integration of storage systems into the grid, the use of mechanisms such as V2G, and smart charging policies for electric vehicles. These strategies improve electricity service while reducing network stress and decreasing network development costs. Future work will focus on the use of more accurate methods for collecting user information, promoting the use of smart chargers connected to the electricity grid and its operators, and enhancing the policies used in this area.
اثر شحن المركبات الكهربائية على اقصى حمل للشبكة الكهربائية والسياسات المتبعة لمواجهتها